Teaching Vocabulary Through Picture Story at The Eight Grade Students of Pesantren Modern Datok Sulaiman Palopo - Sultan Rasilu, Eva Lestari Sultan; Zaenal, Hadijah (JULIET: Journal of English Language and Literature, 2025)
This research aims at finding out whether or not the use of picture story significantly increases the students’ vocabulary at the eighth grade of Pesantren Modern Datok Sulaiman Palopo. The researcher applied pre-experimental design with the pretest, treatment, and the posttest. The population of this research is the eighth grade students of Pesantren Modern Datok Sulaiman Palopo. The total number of population is 120 students who are separated in 4 classes. There are 30 students in every class. The researcher uses purposive sampling technique in determining class VIII A as the sample because based on the interview results with the English teacher, it is found that this class is low in mastering vocabulary. The total number of sample in this research is 30 students. Based on the results of data analysis, the researcher concludes that the use of picture story significantly increases the students’ vocabulary at the eighth grade of Pesantren Modern Datok Sulaiman Palopo. It is supported by the mean score of the posttest (76.17) which is higher than the mean score of the pretest (45.96). Besides, the t-test is 13.76 and the result of significant is 0.00. From the criteria of hypothesis acceptability which said that if t-test or 13.76 0.05, the null hypothesis (H0) is rejected and alternative hypothesis (H1) is accepted. It means that there is significant difference between the results of the pre-test and the post-test.